Theoretical investigation of 2-(iminomethyl)phenol in the gas phase as a prototype of ultrafast excited-state intramolecular proton transfer - Rathawat Daengngern (2018)
© 2016 Elsevier B.V. All rights reserved. Photophysical properties of the smallest o-hydroxy Schiff base, 2-(iminomethyl)phenol (IMP), were elucidated using B3LYP and RI-ADC(2) methods. Cis-enol is the most stable conformation in ground state. Potential energy profiles show that enol-keto tautomerization occurs with a small barrier. However, isomerization from cis- to trans-keto is not possible because of a high barrier. The trans-keto tautomer is only accessible through a conical intersection (CI) after excited-state intramolecular proton transfer (ESIPT). Dynamics results show that cis-enol undergoes ultrafast ESIPT to give cis-keto. Regions of CI may be initiated to yield keto forms through radiativeless process with torsion twist of about 40-50°.